2021
DOI: 10.3390/foods10061287
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Profiling of Pleurotus eryngii and Pleurotus ostreatus Mushrooms Cultivated on Agricultural and Agro-Industrial By-Products

Abstract: The influence of genetic (species, strain) and environmental (substrate) factors on the volatile profiles of eight strains of Pleurotus eryngii and P. ostreatus mushrooms cultivated on wheat straw or substrates enriched with winery or olive oil by products was investigated by headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS). Selected samples were additionally roasted. More than 50 compounds were determined in fresh mushroom samples, with P. ostreatus prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…Some of the compounds identified for the mushroom powder samples without spices were (1) 1-hexacosanol (cas) hexacosanol-1 (10.97% area), (2) 2-heptanol, 5-ethyl-(cas) 5ethyl-2-heptanol (8.29% area), (3) 6-methyl-5-hepten-2-one (15.51% area), and (4) octadecanoic acid (cas) stearic acid (5.81% area). Tagkouli et al [25] and Selli et al [26] identified aromatic compounds in fresh Pleurotus ostreatus mushrooms into groups of (1) eight carbon atoms compounds, (2) alcohols, (3) aldehydes, (4) fatty acids (FAME methyl esters), ( 5) toluene, and ( 6) ketones. e powdering process causes the volatile components of oyster mushroom powder to be dominated by alcohol, furan, and fatty acids and their derivatives.…”
Section: Volatile Component Analysis (Gcms)mentioning
confidence: 99%
“…Some of the compounds identified for the mushroom powder samples without spices were (1) 1-hexacosanol (cas) hexacosanol-1 (10.97% area), (2) 2-heptanol, 5-ethyl-(cas) 5ethyl-2-heptanol (8.29% area), (3) 6-methyl-5-hepten-2-one (15.51% area), and (4) octadecanoic acid (cas) stearic acid (5.81% area). Tagkouli et al [25] and Selli et al [26] identified aromatic compounds in fresh Pleurotus ostreatus mushrooms into groups of (1) eight carbon atoms compounds, (2) alcohols, (3) aldehydes, (4) fatty acids (FAME methyl esters), ( 5) toluene, and ( 6) ketones. e powdering process causes the volatile components of oyster mushroom powder to be dominated by alcohol, furan, and fatty acids and their derivatives.…”
Section: Volatile Component Analysis (Gcms)mentioning
confidence: 99%
“…One of the linear and aromatic aldehydes, hexanal, and benzaldehyde, respectively, were two most common chemicals in related category. While hexanal is associated with rancid and grass aroma at high and low concentrations, respectively, benzaldehyde is responsible for bitter almond, nutty and powdery sensations [17,18] . If phenylalanine degrades oxidatively, benzaldehyde may be arised [18] .…”
Section: Resultsmentioning
confidence: 99%
“…Four different odorants like d‐limonene, 1,8‐cineole, (+)‐3‐carene, and thymol were identified, and only two of them (d‐limonene, 1,8‐cineole) were commonly found. A camphoric aroma is provided by terpenes, and especially d‐limonene molecules supply orange and lemon odors [18,19] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivation of Pleurotus mushrooms depends on both intrinsic factors (i.e., substrate type, pH, C:N ratio, levels of spawning, surfactants, the content of N, C and moisture) and extrinsic factors, which include temperature, relative humidity, luminosity, air composition, and light [30,31,36,58,60,62,63]. The growth and cultivation of mushrooms can be achieved using growth media or substrates, which have a vital impact on the functional, chemical, and sensorial characteristics of mushrooms [58,64,65]. Solid substrates can be used traditionally in cultivating many species of mushrooms for fruiting body formation, which usually needs several months with a non-stable quality of harvested materials [66].…”
Section: General Features Of Pleurotus Ostreatusmentioning
confidence: 99%